Pengaruh Kompleksitas Tugas dan Komitmen Organisasi Pada Kinerja Auditor dengan Tindakan Supervisi Sebagai Variabel Moderasi - Agustini, Ni Made Lina; Dwirandra, A.A. N.B. (E-Jurnal Akuntansi, 2017)
Kantor Akuntan Publik (KAP) is an organization engaged in services with the auditor as a worker. Nowadays, the increasingly widespread need of professional public accountant as an independent party makes the competition among Public Accounting Firm that requires the public accountant to improve its performance to become a qualified, reliable, and able to produce quality audit products. Auditor performance can be influenced by some fakor, including task complexity, organizational commitment, and supervisory actions. This study aims to determine the effect of task complexity and organizational commitment on the performance of auditors with the act of supervision as a moderation variable. The location of the research was conducted at the Public Accounting Firm of Bali Province. Data collection method used was questionnaire with purposive sampling technique and obtained 34 samples. The analysis tool used is Moderated Regression Analysis. The results of this study indicate that the task complexity variables have a negative effect on the performance of auditors, organizational commitment has a positive effect on the performance of auditors. This indicates that the higher organizational commitment owned by an auditor then the auditor's performance will be increased while when faced in a complex task situation in the auditing process, the auditor's performance will decrease. The results of the study also show that supervision actions can weaken the relation of task complexity to auditor performance, but the supervision action is unable to strengthen the relationship of organizational commitment to auditor performance in Public Accountant Office of Bali Province.